THE ENFORCEMENT OF WANPRESTASI ON DEBT RECOGNITION IN DEBT AGREEMENTS: A Case Study of District Court Decision No. 9/Pdt.G.S/2021/Pn.Srl - Fitriana, Fairus Nur; Setiasih, Herma (YURIS: Journal of Court and Justice, 2022)
An agreement is a legal act regarding the property of two parties, in which one party promises to do something, while the other party has the right to demand its implementation. Thus, the relationship arises between the two parties during the agreement. In its form, the cooperation contract or agreement is a series of words in written form that contains promises of the ability to do something. This research is normative law. A normative research initiates by conducting a search on legal materials as a basis for making legal decisions on legal cases. The approach method used is a normative juridical approach. A normative juridical approach is used to provide a qualitative analysis by analyzing the theories, legal principles and law to discussed material. This research indicated that legal consequence of wanprestasi on debt acknowledgement letter in the debt-receivable agreement is a civil lawsuit or a claim for compensation. The efforts made by the creditor is very appropriate for the party who is harmed in debt agreement. According to law, legal remedies are through non-litigation and litigation. It can be concluded that although the agreement is not specifically regulated, the agreement that provides freedom of contract makes more convenient for public to make contracts outside the agreements contained in Book III of the Civil Code.